Targeting RyR Activity Boosts Antisense Exon 44 and 45 Skipping in Human DMD Skeletal or Cardiac Muscle Culture Models - Florian Barthélémy; Richard T. Wang; Christopher Hsu; Emilie D. Douine; Eugene E. Marcantonio; Stanley F. Nelson; M. Carrie Miceli (Elsevier, 2019)
Systemic delivery of antisense oligonucleotides (AO) for DMD exon skipping has proven effective for reframing DMD mRNA, rescuing dystrophin expression, and slowing disease progression in animal models. In humans with Duchenne muscular dystrophy treated with AOs, low levels of dystrophin have been induced, and modest slowing of disease progression has been observed, highlighting the need for improved efficiency of human skipping drugs. Here, we demonstrate that dantrolene and Rycals S107 and ARM210 potentiate AO-mediated exon skipping of exon 44 or exon 45 in patient-derived myotube cultures with appropriate mutations. Further, dantrolene is shown to boost AO-mediated exon skipping in patient-derived, induced cardiomyocyte cultures. Our findings further validate the ryanodine receptors (RyR) as the likely target responsible for exon skip boosting and demonstrate potential applicability beyond exon 51 skipping. These data provide preclinical support of dantrolene trial as an adjuvant to AO-mediated exon-skipping therapy in humans and identify a novel Rycal, ARM210, for development as a potential exon-skipping booster. Further, they highlight the value of mutation-specific DMD culture models for basic discovery, preclinical drug screening and translation of personalized genetic medicines. Keywords: Duchenne muscular dystrophy, combination therapy, dantrolene, dystrophin, exon skipping, armgo, ARM210, muscle, therapy